Secular Trends in the Determinants of Disability Benefits - Wilson, Sven E.; Nguyen, Louis L. (American Economic Review, 2016)
A major justification for devoting resources to the study of public health is the potential to answer questions about the burden of poor health, both in terms of the total burden faced by individuals and the burden placed upon publicly funded social insurance programs. Indeed, the adequate provision of social insurance programs is one of the key policy issues of our day. A potentially fruitful approach in undertaking this effort is to investigate the effects of specific chronic diseases and injuries upon program participation and benefit levels. Ideally, we would like to know something about the total economic costs of individual diseases using theoretically sound willingness-to-pay measures. In practice, however, willingness-to-pay measures cannot be estimated with most available health data. Though this paper cannot pin down anything as ambitious as the total economic burden of disease, it does address the narrower but still important question of what is the burden of chronic illness upon Social Security Disability Insurance (SSDI) payments, and it documents how that burden has shifted between different disease groups over the past century. Furthermore, it addresses, at least to a limited extent, the profound intellectual question of what determines disability and how biomedical, economic, social, and institutional factors determine whether an individual will be disabled. In this paper we begin an exploration of newly collected data on the health conditions and disability benefits of Union Army VeteransI and make comparisons to recipients of disability benefits in more recent tinmes. We find two main results. The first is that there has been a significant shift in the types of diseases that lead to disability, both in terms of prevalence rates and benefit levels. The second is more surprising: the disabled in modern times generally have a greater number of chronic illnesses than did disabled Union Army veterans, even those who were severely disabled. This result implies a way of thinking about disease and disability that deserves more research attention. In short, prior to the advent of modem medicine and the concurrent reductions in the physical demands of work, people became disabled not because they had numerous chronic illnesses (i.e., high rates of co-morbidity), but because individual conditions (even ones as simple as hernias or hemorrhoids) had much more severely debilitating effects on health and upon the capacity to work than those same conditions do today.